A CMOS Image Sensor Integrated with Plasmonic Colour Filters - Chen, Q; Das, D; Chitnis, D; Walls, K; Drysdale, T; Collins, S; Cumming, D (2012)
Multi-pixel, 4. 5 × 9 μm, plasmonic colour filters, consisting of periodic subwavelength holes in an aluminium film, were directly integrated on the top surface of a complementary metal oxide semiconductor (CMOS) image sensor (CIS) using electron beam lithography and dry etch. The 100 × 100-pixel plasmonic CIS showed full colour sensitivities across the visible range determined by a photocurrent measurement. The filters were fabricated in a simple process utilising a single lithography step. This is to be compared with the traditional multi-step processing when using dye-doped polymers. The intrinsic compatibility of these plasmonic components with a standard CMOS process allows them to be manufactured in a metal layer close to the photodiodes. The incorporation of such plasmonic components may in the future enable the development of advanced CIS with low cost, low cross-talk and increased functionality. © 2012 Springer Science+Business Media, LLC.